Principles of removal of endometrial ovarian cysts with particular reference to ovarian reserve - Owczarek, Dariusz; Malinowski, Andrzej (Menopause Review/Przegląd Menopauzalny, 2012)
Endometriosis is defined as extra-uterine occurrence of endometrial glandular cells and endometrial stroma, and still represents a great challenge to gynecologists, especially in respect to fertility and pain. Endometriosis often occurs in ovaries. If you analyze the risk of cystic recurrence, the risk of pain recurrence and the pregnancy rate, you may consider that the laparoscopy is the method of choice in surgical treatment of endometrial cysts; correspondingly, it replaces the classical laparotomy. Many studies have described various techniques of endoscopic treatment of ovarian endometriosis, but it seems that the pseudocapsular enucleation should be the standard in surgical treatment. Every surgery carried out due to an endometrial cyst implies a risk of iatrogenic ovarian damage and, by the same token, a reduction in ovarian reserve. According to the newest clinical data, the best methods of assessing the ovarian reserve are: Antral Follicle Count (AFC) and serum concentration of Anti-Müllerian hormone (AMH). Concentration of AMH is highly correlated with the antral follicle count visible in the ultrasound examination. The evaluation of the serum concentration of FSH, LH, E2 and inhibin have a lower diagnostic value in the assessment of ovarian reserve. Further investigations are necessary to assess the impact of electric energy and of ovarian suture - as methods of achieving hemostasis - on the ovarian reserve.